2013
DOI: 10.1016/j.ijgo.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Adnexal masses encountered during cesarean delivery

Abstract: Adnexal masses encountered during cesarean delivery generally have a favorable prognosis in terms of maternal and fetal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
0
25
0
3
Order By: Relevance
“…But the effects of asymptomatic ovarian masses on the preterm labor rate is unknown, thus more studies are suggested. In recent studies there were no severe neonatal morbidity or mortality mentioned for those who had ovarian mass incidentally diagnosed during cesarean delivery [11].…”
Section: Discussionmentioning
confidence: 98%
“…But the effects of asymptomatic ovarian masses on the preterm labor rate is unknown, thus more studies are suggested. In recent studies there were no severe neonatal morbidity or mortality mentioned for those who had ovarian mass incidentally diagnosed during cesarean delivery [11].…”
Section: Discussionmentioning
confidence: 98%
“…A review of the literature supports MCT as the common histological diagnosis in ovarian cysts removed during pregnancy, as they are functional cysts . These were associated with favorable maternal and fetal outcomes, but as malignancy was discovered in a minority of these patients, their removal as part of cesarean delivery seems advisable . In our study, all non‐cesarean surgeries in pregnant patients were performed via laparoscopy, with gestational age ranging from 5 to 28 weeks.…”
Section: Discussionmentioning
confidence: 75%
“…16,17 These were associated with favorable maternal and fetal outcomes, but as malignancy was discovered in a minority of these patients, their removal as part of cesarean delivery seems advisable. 18,19 In our study, all non-cesarean surgeries in pregnant patients were performed via laparoscopy, with gestational age ranging from 5 to 28 weeks. Indeed, this has previously been demonstrated to confer a safe and practical surgical approach during pregnancy, and our favorable study results support this management.…”
Section: Discussionmentioning
confidence: 99%
“…Hastaların %24'ünde dermoid kist, %19'unda paratubal/paraovaryan kist, %15'inde basit seröz kist, %18'inde müsinöz/seröz kistadenom, %5'inde endometriyoma, %5'inde korpus luteum saptanmıştır. 3 Çalışmadan da görüleceği gibi, gebelikteki adneksiyal kitlelerin nadir bir bölü-münü maligniteler oluşturmaktadır. Bunların 1/3'ü epitelyal over tümörü, 1/3'ü germ hücreli tümör-ler, 1/3'ü ise seks-kord stromal tümörleri ve metastatik tümörleri içermektedir.…”
Section: Discussionunclassified